Integration of Art in Pathology Education Insights from the Faculty of Medicine and Pharmacy - Aslam, Huma; Rashid, Fatima; Malik, Pervaiz Azam; Khan, Muhammad Basharat; Din, Saeed Taj (Journal of Neonatal Surgery, 2025)
Introduction: Traditional pathology education often relies on didactic instruction and visual memorization, which may fail to engage students or support the development of key diagnostic and reflective skills. Objective: To evaluate the impact of art-based learning methods on student engagement, comprehension, diagnostic skill development, and reflective learning in pathology education among students of the Faculty of Medicine and Pharmacy. Methods: This cross-sectional study was conducted at Sahiwal Medical College, Sahiwal during June 2023 to November 2024. The study sample consisted of 285 undergraduate students enrolled in pathology courses. These students represented various academic years within the Faculty of Medicine and Pharmacy and were exposed to at least one form of art-based intervention as part of their pathology instruction. Participation in the study was voluntary, and informed consent was obtained from all students. Results: Out of the 285 students, 273 completed the survey (response rate: 95.8%). Approximately 85% agreed that art-based interventions enhanced their understanding of pathological concepts. Engagement levels were high, with 91% reporting increased motivation through artistic methods. Observational and diagnostic skill development was noted by 73% of participants. Statistically significant differences were observed between medicine and pharmacy students in perceived skill improvement (p < 0.05). Conclusion: It is concluded that integrating art into pathology education positively impacts student engagement, comprehension, and reflective capacity. This approach supports the development of core diagnostic skills while fostering empathy and creativity.